(untitled) (Revista Iberoamericana de Estudios Municipales, 2023)
Armed conflict can have influence on territories in different aspects. One of them is related with the agricultural use of the land. Particularly about capitalist and peasant uses. This article looks for causes that explain the differences in the change of agricultural land uses in two municipalities of the east of Colombia (Mesetas and Vistahermosa) as an effect of the armed conflict between 1998 and 2014. This work used a focused and structured comparison to reflect, through the behavior of some variables chosen, the differences between capitalist and peasant crops under an armed conflict period. This work found that the central reason for the differences between the crops of the municipalities was the differentiated presence of armed actors. Thus, although the municipalities in principle showed a tendency to adapt the uses to the conflict, after the most intense period, in Mesetas the conflict generated decrease while in Vistahermosa capitalist crops grew.